2016
DOI: 10.1002/ece3.2025
|View full text |Cite
|
Sign up to set email alerts
|

Belowground responses to elevation in a changing cloud forest

Abstract: Few studies have investigated how soil fungal communities respond to elevation, especially within TMCF (tropical montane cloud forests). We used an elevation gradient in a TMCF in Costa Rica to determine how soil properties, processes, and community composition of fungi change in response to elevation and across seasons. As elevation increased, soil temperature and soil pH decreased, while soil moisture and soil C:N ratios increased with elevation. Responses of these properties varied seasonally. Fungal abunda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 83 publications
(135 reference statements)
6
35
0
Order By: Relevance
“…, Looby et al. , Geml ). For example, along other elevation gradients, the presence of EM and endophytic fungal hosts explained correlations in plant and fungal β‐diversity (Geml et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Looby et al. , Geml ). For example, along other elevation gradients, the presence of EM and endophytic fungal hosts explained correlations in plant and fungal β‐diversity (Geml et al.…”
Section: Discussionmentioning
confidence: 99%
“…Fungal α‐diversity increased with a 4°C temperature increase across an elevation gradient in tropical montane cloud forest in Costa Rica, although decreased soil moisture also explained this diversity pattern (Looby et al. ). The majority of fungal diversity studies on mountain gradients have focused on specific phyla, reporting high variation in α‐diversity patterns (Geml et al.…”
Section: Discussionmentioning
confidence: 99%
“…Bryant et al (2008) found that Acidobacteria decreased in richness over a change of 1000 m elevation in the Rocky Mountains. Similarly mixed results have been found for Fungi, with evidence for greatest richness at mid-elevations due to range overlap (Bahram et al 2012, Coince et al 2014, Miyamoto et al 2014, lack of change with elevation (Zimmerman and Vitousek 2012, Coince et al 2014, Jarvis et al 2015, decreased richness at higher elevations (Looby et al 2016), or increased richness at higher elevations (Pellissier et al 2014). Fewer studies have examined Archaea, but work on two Japanese mountains found a mid-elevation peak in OTU richness (Singh et al 2012, Singh et al 2016).…”
Section: Controls Over Microbial Richnessmentioning
confidence: 90%
“…For Fungi, previous studies have examined how the distribution and diversity at the level of all Fungi (Zhang et al 2013), at the functional group level (Bahram et al 2012) and at the phylum level (Looby et al 2016) change over an elevational gradient, and found that changes across the gradient became more apparent as lower taxonomic levels and/or ecological trait differences were accounted. We see similar patterns in our system, and changes in richness across this soil climosequence were clearly linked to resources for each group.…”
Section: Controls Over Microbial Richnessmentioning
confidence: 99%
See 1 more Smart Citation